PENGEMBANGAN BAHAN AJAR ECO GARBAGE ENZYME SEBAGAI MEDIA PEMBELAJARAN DI MASA PANDEMI COVID-19 - Pertiwi Indah Lestari; Rika Riyanti; Warda Murti; Ernawati Ernawati; Rizki Amalia Nur; Muhammad Ilham (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to develop teaching materials for eco garbage enzymes as learning media. The product produced was teaching materials for making eco garbage enzymes of liquid organic fertilizer. The research model employed was the 4D model, which comprises four stages, but only the development stage used in this study. The instruments used in this study were validation sheets and questionnaires to measure the validity and practicality of the developed eco garbage enzyme products.Two experts validated the product then analyzed it on the Gregory test. The value obtained was 1, which means the product was valid and feasible to use. Based on product used observation, the practicality value showed 4,6 means the product had used as a whole. According to learning outcomes, the product effectivity was 78.25 % in the high to very high categories (completeness equal to 75%). In addition, the positive response from students was 94.09%, this indicates that the teaching materials are effective to use as learning media